(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2020)
A field investigation was carried out from January 2015 to December 2017 to study the status of some lycaenid butterflies in some selected forest areas of Bangladesh. A total of 6,724 lycaenids was recorded from Butterfly Research Park at Bhawal National Park, Gazipur; Madhupur National Park, Tangail; Satchori National Park and Rema-Kalenga Wildlife Sanctuary of Habigonj. The dominant species was Arhopala pseudocentaurus with 21.85% relative frequency and the least abundant species was Rathinda amor with 0.75% relative frequency. Butterfly Research Park showed the maximum number of butterfly individuals with a covariance of 40% followed by Madhupur National Park (37%), Rema-Kalenga Wildlife Sanctuary (13%), and Satchori National Park (10%). A significant difference (F = 3.52, p-value = 0.02) has been assessed using „One-way ANOVA‟ test. The difference in the availability of butterflies in different habitats indicated the differences in plant diversity among the forests. Lycaenid butterflies displayed highest abundance (13.19%) in December and lowest (5.38%) in October. There was no significant difference (F = 0.72, p-value = 0.71) among different months throughout the study period in overall species abundance though highest number was recorded in December. The abiotic factors (viz. temperature and relative humidity etc.) influence the presence of butterflies. Lycaenid butterflies demonstrated the highest abundance (887) in 26.9°C along with 64% relative humidity whereas the least abundance (362) has been recorded at 31.7°C with 77% relative humidity. The significant negative correlation was found in between lycaenid abundance and temperature (r = ─ 0.45, pvalue = 0.14), and between lycaenid abundance and relative humidity (r = ─ 0.19, p-value = 0.54). The butterfly population increased with decreasing average temperature and relative humidity during the study period. This investigation reveals the differences in the availability of lycaenid butterflies in relation to the differences in plant population and also the effect of abiotic factors in the forest areas. J. Biodivers. Conserv. Bioresour. Manag. 2019, 5(2): 19-32